Role of Host and Bacterial Lipids in Pseudomonas aeruginosa Respiratory Infections - Constantino-Teles, Pamella; Jouault, Albane; Touqui, Lhousseine; Saliba, Alessandra Mattos (Frontiers in Immunology, 2022)
The opportunistic pathogen Pseudomonas aeruginosa is one of the most common agents of respiratory infections and has been associated with high morbidity and mortality rates. The ability of P. aeruginosa to cause severe respiratory infections results from the coordinated action of a variety of virulence factors that promote bacterial persistence in the lungs. Several of these P. aeruginosa virulence mechanisms are mediated by bacterial lipids, mainly lipopolysaccharide, rhamnolipid, lipoproteins, and outer membrane vesicles. Other mechanisms arise from the activity of P. aeruginosa enzymes, particularly ExoU, phospholipase C, and lipoxygenase A, which interfere with host lipid signaling pathways. Moreover, host phospholipases, such as cPLA2alpha and sPLA2, are also activated during the infectious process and play important roles in P. aeruginosa pathogenesis. These mechanisms affect key points of the P. aeruginosa-host interaction, such as: i) biofilm formation that contributes to bacterial colonization and survival, ii) invasion of tissue barriers that allows bacterial dissemination, iii) modulation of inflammatory responses, and iv) escape from host defenses. In this mini-review, we present the lipid-based mechanism that interferes with the establishment of P. aeruginosa in the lungs and discuss how bacterial and host lipids can impact the outcome of P. aeruginosa respiratory infections.